Unfolding of telecommuting's effects in organizations: performance, commitment, and mechanisms of action - Onder, Casey Claire, author; Kraiger, Kurt, advisor; Gibbons, Alyssa, advisor; Dik, Bryan, committee member; Henle, Chris, committee member (Colorado State University. Libraries, 2016)
Telecommuting is an increasingly popular flex work arrangement, and there is controversy regarding its effects on employee performance and commitment. There is likewise lack of clarity regarding mechanisms of action. While autonomy has received support as a mediator of telecommuting’s relationship with several work outcomes, the role of work-life balance as a mediating mechanism remains untested, and prior research is largely cross-sectional. The present study drew on instrumental as well as signaling-and-exchange perspectives of telecommuting’s benefits to test the simultaneous influence of mediators of job autonomy and work-life balance support perceptions on outcomes of supervisor-rated performance, affective commitment, and intent to stay. I proposed and tested a theoretical model of telecommuting’s impact on these outcomes using lagged self-report and supervisor-rated performance data from 2,682 full-time managerial and administrative employees in an organization where telecommuting was broadly offered as a flexible work policy. Results indicated that telecommuting had a positive impact on affective commitment and intent to stay through perceptions of work-life balance support. Perceptions of autonomy and job performance, however, were unaffected. Results suggest that work-life balance support is an important mediator of telecommuting’s impact on commitment-related outcomes, and that where telecommuting is perceived as a form of work-life balance support, performance may be unaffected. Results of this study extend the literature on telecommuting’s mechanisms of action and from an organizational perspective, suggest that the “value added” of work-life balance supportive telecommuting arrangements is more likely to come in the form of enhanced commitment versus performance.